2021
DOI: 10.3389/fimmu.2021.620709
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From the Clinical Presentation of Common Variable Immunodeficiency Disorders: A Systematic Review and Meta-Analysis

Abstract: BackgroundDiagnostic delay in common variable immunodeficiency disorders (CVID) is considerable. There is no generally accepted symptom-recognition framework for its early detection.ObjectiveTo systematically review all existing data on the clinical presentation of CVID.MethodsPubMed, EMBASE and Cochrane were searched for cohort studies, published January/1999-December/2019, detailing the clinical manifestations before, at and after the CVID-diagnosis.ResultsIn 51 studies (n=8521 patients) 134 presenting and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 92 publications
1
30
0
2
Order By: Relevance
“…It is generally accepted that low levels of IgA, IgM, and IgG predispose to respiratory bacterial and viral infections. The high incidence of URI and pneumonia in our patients with SIgED is in keeping with that reported for CVID [ 8 , 9 , 29 ], SIgGD [ 8 ], IgGSD [ 9 , 10 ], SIgAD [ 11 , 12 ], and SIgMD [ 13 , 14 ]. The mechanism by which an SIgED may also predispose to lung infections remains to be elucidated.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…It is generally accepted that low levels of IgA, IgM, and IgG predispose to respiratory bacterial and viral infections. The high incidence of URI and pneumonia in our patients with SIgED is in keeping with that reported for CVID [ 8 , 9 , 29 ], SIgGD [ 8 ], IgGSD [ 9 , 10 ], SIgAD [ 11 , 12 ], and SIgMD [ 13 , 14 ]. The mechanism by which an SIgED may also predispose to lung infections remains to be elucidated.…”
Section: Discussionsupporting
confidence: 90%
“…It is generally assumed that in CVID patients, recurrent airway infections and persistent airway inflammation can lead to a vicious circle airway remodeling process resulting in bronchiectasis [ 43 ]. A recent analysis of existing data on the clinical presentation of CVID found that bronchiectasis was present in the CT scan in almost one-third of patients (28%, 95% CI 18–40) [ 29 ]. Bronchiectasis has been found in up to 14% of SIgAD patients and is more commonly reported when associated with IgG subclass deficiency [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations